Forced coplanarity of dithienofluorene-based non-fullerene acceptors to achieve high-efficiency organic solar cells. Issue 30 (15th July 2019) - Cao, Fong-Yi; Huang, Po-Kai; Su, Yen-Chen; Huang, Wen-Chia; Chang, Shao-Ling; Hung, Kai-En; Cheng, Yen-Ju
Abstract : This work clearly demonstrates the importance of chemical planarization in designing high-performance nonfullerene acceptors and the ternary-blend device using PBDB-T:DTFT9-FIC:PC71 BM achieved a high PCE of 11.82%. Abstract : Ladder-type structures have been the key element for high performance non-fullerene acceptors (NFAs). In this work, two dithieno[3, 2- b :6, 7- b ′]fluorine (DTF)-based nonfullerene acceptors, non-bridged DTFT5-FIC and carbon-bridged DTFT9-FIC, with an identical conjugated backbone were designed and synthesized for investigation of the planarization effect. The chemical rigidification with forced coplanarity indeed plays a pivotal role in determining the molecular properties. Compared to the non-bridged open-chain DTFT5-FIC counterpart, the nonacyclic ladder-type DTFT9-FIC with a fully planarized backbone exhibits higher thermal stability, bathochromic absorption and higher electron mobility. The devices using PBDB-T as the p-type polymer and fully planar DTFT9-FIC as the acceptor showed a high efficiency of 9.58%, which is superior to that of the device using the partially planar DTFT5-FIC material (5.45%). By incorporating PC71 BM as the second acceptor to enhance the absorption at shorter wavelengths, optimize the morphology and facilitate electron transport, the ternary-blend device using PBDB-T:DTFT9-FIC:PC71 BM achieved the highest PCE of 11.82% with a V oc of 0.88 V, a higher J sc of 20.59 mA cm −2, and an FF of 65.27%.